Impact of Surgeon Specialty on Ankle Arthrodesis Readmission, Complication, and Infection Rates: A Medicare Analysis - Devon Nixon MD; Hyunkyu Ko PhD; Brook Martin PhD (Foot & Ankle Orthopaedics, 2024)
Category: Ankle Arthritis; Other Introduction/Purpose: Ankle arthrodesis (AA) remains a reliable treatment option to address end-stage ankle pathology in appropriately selected patients. When successful, AA surgeries can yield high patient satisfaction and marked improvements in patient-reported outcomes. AA can be performed by orthopedic surgeons (MD or DO) and non-orthopedic surgeons (DPM). However, no prior study has compared surgical safety indicators of AA based on surgeon specialty. Methods: Utilizing Medicare claims from 2016 to 2019, we retrospectively identified patients ≥65 years of age who underwent AA based on CPT coding. Patients on Medicare Health Maintenance Organization (HMO), End-Stage Renal Disease (ESRD), age under 65, and dual-eligible patients were excluded. Within this dataset, provider specialty was identified from Part B (provider claim), allowing for comparisons between orthopedic and non-orthopedic surgeons. We compared groups based on readmission, all-complication, and infection rates within 1-year of AA using logistic regressions controlling for age, sex, race, and Charlson Comorbidity Index (CCI). To help mitigate bias, we also performed a propensity matched model with the same variables. Data were reported as percentage point (PPT) differences (95% CI) between groups, with a positive number indicating higher rate of complications among patients treated by non-orthopedic surgeons. Results: During our timeframe, 3,274 AA procedures were performed by orthopedic surgeons and 614 by non-orthopedic surgeons. Non-orthopedic surgeons performed AA on patients with greater comorbidities (CCI scores: 0, 1, 2+: 34.7%, 20.4%, 44.8%) compared to orthopedic surgeons (CCI scores: 28.2%, 16.4%, 55.4%) (p< 0.001). AA performed by non-orthopedic surgeons, compared to orthopedic surgeons, had higher all-cause readmission rates (46.1% vs. 39.4%, p=0.008), all-complication rates (72.3% vs. 63.7%, p< 0.001) as well as complications with readmission (49.9% vs. 43.9%, p=0.019) and without readmission (55.0% vs. 43.1%, p< 0.001). All-cause infection risk within 1-year was higher in non-orthopedic surgeons (16.2% vs. 9.3%, p< 0.001), and persisted in our propensity-matched analyses (6.9 ppt higher (CI: 2.2, 11.7), p=0.004). Differences in the other safety measures were largely attenuated in the propensity-matched analysis. Conclusion: AA performed by non-orthopedic surgeons had greater all-complication, readmission, and infection rates as compared to AA done by orthopedic surgeons. Infection risk most notably persisted in analyses controlling for comorbidities. Infection following AA can lead to devastating outcomes for patients. The implication of findings like these will require further study to better understand how foot and ankle care is administered to patients at a policy-level.